Perception of Inbound Backpackers towards Urban Superstructure: A Case in Jakarta (Indonesia) - Hendijani, Roozbeh Babolian (Turizam, 2018)
A tourist’s experience is the factor that would determine the satisfaction of a trip and it is important for destinations to achieve success in the highly competitive tourism marketplace. Backpacking as one of the modes of travelling is getting attention among scholars. In Indonesia, the numbers of backpackers are increasing year by year; however there is still a lack of study about their satisfaction levels based on their backpacking experience, mainly due to the misconception that this segment of the market has low value. Therefore, the objectives of this research are to identify the most affecting experience of backpackers’ satisfaction based on superstructure in Jakarta, and to know the effect of satisfaction on their decision to revisit. The target of this research is inbound backpackers from Jakarta, Indonesia. This research employs a quantitative method with the usage of self-administered questionnaires to gather the data from 160 backpackers in Jakarta’s international airport and some tourist attractions around Jakarta. Different analyses such as exploratory factor analysis, multiple linear regression, and descriptive analysis were employed. The results of this study identified some factors which have a significant impact on satisfaction. It is proposed that for the sustainability of tourism development, future planning should consider the importance of backpackers as a considerable target market. The findings would be helpful to various stakeholders such as marketers and hospitality businesses in order to understand and improve tourists’ visit experience in future.